Hand Surgeon Posture: An Evaluation and Factors That Affect It - Johnson, Evan P.; Kothari, Ezan A.; Zumsteg, Justin W.; Romero, Andrew B.; Schwartz-Fernandes, Francisco A.; Lewellyn, Brett J. (Journal of Hand and Microsurgery, 2023)
Objective Approximately 68% of orthopaedic surgeons report occupational related musculoskeletal pain, with back pain being the most common. Poor posture while operating has been proven to contribute to these high rates of musculoskeletal pain. There is little research regarding intraoperative surgeon posture within the field of hand and upper extremity surgery. This prospective study aims to investigate and analyze hand surgeon posture in the operating room.Methods Posture of three hand surgeons was recorded using the UPRIGHT GO posture tracking device while performing a prospective series of 223 hand and upper extremity surgeries. This device reports posture in terms of overall percentage of time spent slouched versus upright. For this cohort of 223 cases, data were collected including surgical procedure, whether the surgery was performed in a seated or standing position, whether or not loupes were worn during the procedure, and if the surgeon was the primary or assistant surgeon. These data were then analyzed to look for any contributing factors to poor posture.Results The three hand surgeons in this study spent an average of 40.3% of their time slouched while operating. The average percentage of time slouched was significantly greater with the use of loupes versus no loupes. Additionally, mean time slouching was slightly increased when the surgeon was seated and also when the surgeon was acting as the assistant surgeon.Conclusion The three orthopaedic hand surgeons in our study spent a significant portion of their operative time slouched. The main variable associated with a significant risk of poor surgical posture was wearing loupes. Slight increases in slouching were seen with operating while seated and as the assistant surgeon. Surgeon awareness of these variables, as well as techniques to improve surgeon posture, should be developed in order to help contribute to better surgeon posture within the field of hand surgery.
Keywords: back pain; hand surgery; neck pain; orthopaedics; posture